The comparison of prosthetic materials used for abdominal wall defects or hernia - Arab, Adnan; Sahin, Mustafa; Erbilen, Mustafa; Orakci, Vahap; Bulbuloglu, Ertan; Ertas, Ertugrul (Annals of Medical Research, 2021)
None